Avaliação da perda do excesso de peso e da composição corporal após 12 meses de bypass gástrico em Y-de-Roux - Escobar, Fabrícia Teixeira (Universidade do Vale do Rio dos Sinos, 2011)
Introduction: Regarding the evaluation of excess weight loss, the distribution of body fat and lean mass is the most appropriate method for assessing changes in body composition in bariatric patients. Aim: To evaluate the excess weight loss and the body composition of patients undergoing RYGB at Hospital de Clínicas de Porto Alegre (HCPA). Methods: A retrospective cohort study was conducted in 39 patients (36 women and 3 men) undergoing RYGB between 2009 and 2011. The following variables were assessed: age, body mass index (BMI), excess weight loss after 1, 6 and 12 months and body composition (% body fat, % lean mass and % total body water) 12 months after RYGB. Results: Mean age was 42,67+9,6 years old. Prior to the surgery, mean weight was 128,46+17,98 Kg, BMI 48,41+6,13 Kg/m² and initial excess weight 61,89+16,03 Kg. Excess weight loss after 1, 6 and 12 months postoperative was 24,28+8%, 57,31+12,2% and 74,53+15,6%, respectively. By the 12th month following surgery, mean body fat was 36,61+6,61%, lean mass 63,18+7,53% and total body water 47,36+4,13%. Conclusions: This study demonstrated that RYGB is an effective method for excess weight loss for obesity class II and III, primarily through fat body loss.
Keywords: Obesidade mórbida; Cirurgia bariátrica; Bypass gástrico em Y-de-Roux; Composição corporal; Morbid obesity; Bariatric surgery; Roux-en-Y gastric bypass; Body composition